Sustainable fashion dress for all: brand awareness / Azrul Harith Abdullah - Abdullah, Azrul Harith (Faculty of Art and Design, 2020)
A public brand awareness that aimed to change people's lifestyle in fashion and to promote sustainable ways of reducing water consumption and waste generation.